2017
DOI: 10.1371/journal.pone.0186047
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ribosomal proteins in normal and cancerous human prostate tissue

Abstract: Few quantifiable tissue biomarkers for the diagnosis and prognosis of prostate cancer exist. Using an unbiased, quantitative approach, this study evaluates the potential of three proteins of the 40S ribosomal protein complex as putative biomarkers of malignancy in prostate cancer. Prostate tissue arrays, constructed from 82 patient samples (245 tissue cores, stage pT3a or pT3b), were stained for antibodies against three ribosomal proteins, RPS19, RPS21 and RPS24. Semi-automated Ox-DAB signal quantification usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 23 publications
5
40
0
Order By: Relevance
“…All proteins present in Group 1 show increased abundance in cancer.These are ribosomal proteins that participate in biological processes such as translational elongation and protein localization to organelle (based on gene ontology) and belong to the KEGG ribosome pathway. This is in agreement with previous studies, showing that various ribosomal proteins are up-regulated in prostate cancer[24,25]. Ribosomal protein-based cancer signature has been recently proposed based on the expression of ribosomal proteins in several human tissues and primary cells[26].…”
supporting
confidence: 92%
“…All proteins present in Group 1 show increased abundance in cancer.These are ribosomal proteins that participate in biological processes such as translational elongation and protein localization to organelle (based on gene ontology) and belong to the KEGG ribosome pathway. This is in agreement with previous studies, showing that various ribosomal proteins are up-regulated in prostate cancer[24,25]. Ribosomal protein-based cancer signature has been recently proposed based on the expression of ribosomal proteins in several human tissues and primary cells[26].…”
supporting
confidence: 92%
“…Major components of the ribosome (ribosomal proteins e.g. RPS-19, -21, -24 and ribosomal RNA) are upregulated in prostate cancer (PCa) [2,3]. BRF1 expression is elevated and associated with poor prognosis in hepatocellular, breast and gastric cancers [4][5][6] but its role in PCa remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the mutations of RPL18A and RPL31 have been proven to be associated with Diamond-Blackfan anemia (DBA) [58], and RPL15 was demonstrated as a new gene involved in DBA [59], which may decrease the blood supply to myocardial cells to some degree. Results from Arthurs C et al suggested that expression of RPS21 increased in in malignant tissue and may serve as biomarkers for cancer [60]. Similarly, RSL21 has been reported may be a biomarker of cervical intra-epithelial neoplasia 1 [61], and loss of the heterozygosity and decreased expression of RPL14 might be an earlier event in the tumorigenesis of the esophagus [62].…”
Section: Hub Genes Of the Ppi Networkmentioning
confidence: 94%